Incidental Durotomy in Lumbar Spine Surgery; Risk Factors, Complications, and Perioperative Management. Issue 6 (15th March 2021) - Hassanzadeh, Hamid; Bell, Joshua; Bhatia, Manminder; Puvanesarajah, Varun
Abstract : Incidental durotomy (ID) can occur in up to 14% of all lumbar spine surgeries. The risk of this complication is markedly higher among elderly patients with advanced spinal pathology. In addition, revision cases and other more invasive procedures increase the risk of ID. When unrepaired, IDs can increase the risk of developing meningitis and can lead to the formation of cerebrospinal fluid fistulas and pseudomeningoceles. Intraoperative recognition and repair are essential to ID management, although repair techniques vary considerably. Although primary suture repair is considered the "benchmark, " indirect repair alone has shown comparable outcomes. Given the concern for infection after ID, many have indicated for prolonged prophylactic antibiotic regimens. However, there is little clinical evidence that this is necessary after adequate repair. The addition of subfascial drains have been shown to promote wound healing and early ambulation, whereas no consensus on duration of indwelling drains exists and such management is largely case dependent. Early ambulation after surgery has not shown to be associated with increased risk of further ID complications and decreases rehabilitation time, length of stay, and risk of venous thromboembolism. However, there remains a role for conservation mobilization protocols in more severe cases where notable symptoms are observed.